Analisis Strategi Pemasaran Pada The Logoh Smoothies Cafe Di Tenggarong - Erwinsyah, Erwinsyah; Abni, Dinda Rahmah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2020)
Abstract : The purpose of this study is first to find out the right marketing strategy to be applied to The Logoh Smoothies Café. Second, to find out the position of The Logoh Smoothies Café in the SWOT diagram. The analytical tool used in this study is the SWOT method. The number of respondents in this study was 44 respondents. Based on the SWOT research that researchers have done at The Logoh Smoothies Café Tenggarong, the following conclusions can be obtained: (1) Calculation of (Strength) - (Weaknesses) = -0.773, meaning that The Logoh Smoothies cafe has a weakness greater than strength. (2) Calculation of (Opportunities) - (Threats) = 0.25, meaning that The Logoh Smoothies café has a greater chance of threats. From the SWOT matrix the position / strategy of The Logoh Smoothies Café is currently in the Turn Around strategy position located in quadrant III. The focus of the company's strategy is to support the Turn Around Strategy policy. Turn Around Strategy is a strategy that reverses negative trends now. The strategy that must be implemented is to take advantage of opportunities and minimize weakness / WO Strategy with the following policies: (1) Conducting product innovations and increasing menu variations, especially snacks / desert through the use of promotions on social media to increase buyer / community interest. (2) Optimizing promotions such as giving discounts on certain packages / hours / additional bonus promos / certain events to increase the number of buyers by maximizing promotions on social media. (3) Increasing supporting facilities through the addition of facilities such as café name signposts, wifi, and kitchen to attract buyers and increase sales. Keywords: Strength, Weakness, Opportunity, Threat, SWOT Analysis, Turn Around Strategy